Halal Food Literacy: Conceptual Framework, Dimension, and Scale Development - Miftakhul Khasanah; Basu Swastha Dharmmesta; Bayu Sutikno (Faculty of Economics, Universitas Islam Indonesia, 2023)
This study aims to develop the Halal Food Literacy scale (HFL) concept and measurement. The concept of HFL in this study is based on the concept of literacy for consumers. In this case, the SDGs are the theoretical basis for building the HFL concept. Cognitive aspects related to Bloom's concept of Taxonomy were used as the basis for compiling this concept. The study includes four stages: developing, compiling, and describing the concept of Halal Food Literacy based on literature studies, interviews, discussions with experts and scholars, drafting items, testing the validity of the contents, and lastly, data testing with exploratory factor analysis. The results of the scale test revealed that there are four HFL factors, namely Halal awareness, Halal knowledge, Behavioral beliefs, and halal-related label beliefs. These four factors contributed 69.758% of the general variant and 57.828% of the variance from 11 items.